The Influence of Financial Literacy and Risk Preferences on Cryptocurrency Investment Choices - Megha Upreti; Stephanie; setyowati, Widhy (Blockchain Frontier Technology, 2024)
This study aims to describe the overview of financial literacy, risk preferences, and investment decisions, as well as to analyze the influence of financial literacy and risk preferences on cryptocurrency investment decisions among millennials in Tangerang City. The research sample consisted of 95 respondents, selected using purposive sampling technique. Data was collected through a questionnaire with a Likert scale format. The collected data was then analyzed using Partial Least Square (PLS). The results indicate that financial literacy and risk preferences among cryptocurrency investors in Tangerang City are at a very high level. The high financial literacy and risk preferences positively contribute to cryptocurrency investment decisions. Hypothesis testing shows that both financial literacy and risk preferences have a positive and significant impact on cryptocurrency investment decisions. This study has implications for efforts to improve the rationality of cryptocurrency investment decisions to avoid undesirable losses, such as selecting cryptocurrencies with less volatile price fluctuations or diversifying portfolios by combining cryptocurrencies with conventional assets like stocks, bonds, or mutual funds.